(Implementation and Development of HACCP System on Food Industry in Indonesia) - Agus Sudibyo; Sri Esti Rahayu; M Maman Rohaman; Indra Neffi Ridwan; Shinta D. Sirait; Nirwana Aprianita; Dwi Sutrisniati; Ressytustra - (Balai Besar Industri Agro, 2001)
Research on implementation and development hazard analysis critical control point(HACCP) system on food safety on facing international trde and globalization .the methods used was based on descriptive analysis ,that are problem identification of food safety system issue on small and medium industry (SMI'S) ,selection and empowerment to SMI'S training and guiding in food safety system to SMI'S implementing of HACCP management system in SMI's ,food safety auditing based on food safety system to SMI's were still weak and need to be improved in terms of good manufacturing practice (GMP) facilities ,sanitation and personnel hygiene awareness ,responsibility and commitment on food safety system the food safety audit resulted that were five SMIs have met foodsafety plus requirements.